Early Orthodontic Intervention with Eruption Guidance Appliances for Class II Malocclusion: Evidence Mapping Through a Scoping Review - Putu Swastiantari; Arlette Suzy Setiawan (Maranatha Christian University, 2024)
Introduction: Class II malocclusion is a prevalent orthodontic condition in children that can cause both functional and esthetic challenges if not addressed early. The early mixed dentition period offers a critical window for interceptive treatment. Eruption guidance appliances (EGAs) are removable functional devices designed to direct tooth eruption and potentially stimulate favorable skeletal growth. This scoping review aims to map existing evidence on the use of EGAs in treating Class II malocclusion during early mixed dentition. Methods: Following the PRISMA-ScR framework, a comprehensive literature search was conducted in PubMed, Scopus, ScienceDirect, and ProQuest up to July 2025. Studies were selected based on inclusion criteria involving children aged 6–9 years with Class II malocclusion treated using EGAs, with reported skeletal and/or dentoalveolar outcomes. Data were extracted on study design, population, intervention protocols, outcomes, and conclusions. Results: Five eligible studies were included, comprising randomized controlled trials, cohort studies, and case report. Most reported significant dentoalveolar improvements such as reduced overjet, overbite, and molar relationship correction. Skeletal changes were modest but consistent, notably in mandibular advancement and ANB angle reduction. Discussion: EGAs demonstrated favorable outcomes by enhancing dental development and moderately influencing skeletal growth. However, study heterogeneity, limited sample sizes, and short follow-up durations were common limitations. Conclusion: EGAs are promising interceptive tools for early Class II correction, offering non-invasive benefits in guiding eruption and promoting mild skeletal adaptation. Further well-designed longitudinal trials are needed to confirm long-term effectiveness and establish clinical protocols.